A compreensão da definição freudiana do conceito de pulsão sexual para a compreensão do conceito de sexualidade humana - Mouammar, Christiane Carrijo Eckhardt [UNESP] (My University, 2010)
This article approaches the definition of sexual drive proposed by Freud in the Three Essays and how the psychoanalytic conception of human sexuality has been theoretically presented from this first exposition: both as a construct of the species and as an individual construct. It seeks to show how the very metapsychological definition of drive (Trieb) – in 1905 and also in Freud’s 1915 Instincts and their Vicissitudes – interlaced biological contributions and the psychoanalytic clinic in the formulation of an original concept of the human sexuality. The paper also discusses how, because of this duplicity, there is sometimes a developmental interpretation of sexuality in the Three Essays. In the first two of the Three essays, Freud tried to expand the possibilities of sexual behavior, analyzing the drives in the diversity of perversions and in children’s sexuality, while in the third essay the focus was on the adult sexual drive from the moment it organizes itself around an object (hence being no longer auto-erotic) and the reproduction function. Certain experts have occasionally questioned whether the 1905 article attributed a biological teleology to the human sexuality by assigning reproduction as the eventual purpose of the sexual drive – that is, a reproductive goal achieved through the sexual intercourse (coitus). Our study seeks to show how the physiological point of view proposed by Freud in his 1915 article on Instincts sheds some light on how the very biological origin of the drives denies this supposed exclusive reproductive purpose of sexuality. The duplicity of Freud’s concept of drive – as expressed in the enigmatic sentence where he states that this is a concept situated on the border between the psychical and the physical – is then discussed taking into account this intercrossing between the biological and the psychical presented in the Three Essays. The points of view proposed by Freud in 1915 for the definition of the concept of drive – the physiological and the biological points of view – are suggested as conceptual tools to the understanding of this twofold character of human sexuality, according to psychoanalysis.

Este artigo aborda a definição de pulsão sexual proposto por Freud em Três Ensaios e como a concepção psicanalítica da sexualidade humana vem sendo teoricamente apresentada a partir desta primeira exposição: tanto como uma construção da espécie e como uma construção individual. Procura mostrar como a própria definição metapsicológica de pulsão (Trieb) - em 1905 e também em Instintos e suas Vicissitudes, Freud, 1915 - entrelaçou contribuições biológicas e clínica psicanalítica na formulação de um conceito original da sexualidade humana. O artigo também discute como, por causa desta duplicidade, às vezes há uma interpretação desenvolvimentista da sexualidade nos Três Ensaios. Nos dois primeiros dos Três Ensaios, Freud tentou expandir as possibilidades de comportamento sexual, analisando as pulsões na diversidade das perversões e na sexualidade das crianças, enquanto que no terceiro ensaio o foco era a pulsão sexual do adulto a partir do momento em que se organiza em torno de um objeto (portanto não sendo auto-erótico) e a função de reprodução. Alguns especialistas ocasionalmente questionaram se o artigo 1905 atribuiu uma teleologia biológica à sexualidade humana, através da atribuição da reprodução como finalidade eventual da pulsão sexual - ou seja, uma meta reprodutiva alcançada através da relação sexual (coito). Nosso estudo pretende mostrar como o ponto de vista fisiológico proposto por Freud em seu artigo de 1915 sobre Instintos lança alguma luz sobre como a própria origem biológica das pulsões nega essa suposta finalidade exclusiva de reprodução da sexualidade.
Keywords: Sexual drive; Human sexuality; Physiological point of view; Biological point of view; Freudian metapsychology; Psychoanalytic epistemology; Pulsão sexual; Sexualidade humana; Ponto de vista fisiológico; Metapsicologia freudiana; Epistemologia psicanalítica